2003
DOI: 10.1039/b302751a
|View full text |Cite
|
Sign up to set email alerts
|

The base sequence dependent flexibility of linear single-stranded oligoribonucleotides correlates with the reactivity of the phosphodiester bond

Abstract: The effect of base sequence on the structure and flexibility of linear single-stranded RNA molecules and the influence of the base sequence on phosphodiester bond reactivity have been studied. Molecular dynamics simulations of 2.1 ns were carried out for nine chimeric oligonucleotides containing only one unsubstituted ribo unit, all the rest of sugars being 2'-O-methylated. The base sequence has recently been reported to make a big contribution to the reactivity of these compounds. A detailed examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Cleavage products were resolved on denaturing 18% PAAG. To identify the cleavage sites (here and in all cleavage experiments), the probes were run in parallel with ladders produced by RNase T1 (28) and 2 M imidazole buffer, pH 7.0 (5). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage products were resolved on denaturing 18% PAAG. To identify the cleavage sites (here and in all cleavage experiments), the probes were run in parallel with ladders produced by RNase T1 (28) and 2 M imidazole buffer, pH 7.0 (5). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that base stacking strongly affects the reactivity of RNA phosphodiester bond towards cleavage (5,6). Cleavage of single-stranded RNA oligomers, as well as of RNA hairpin-loops and bulge-loops by imidazole buffer (7), metal ions (811), amines (12) or detergents (13) has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic-resolution studies of ssRNA are scarce: at present only one isosequential ssRNA and ssDNA sequence has been characterized by homonuclear NMR methods and shown to possess properties reminiscent of A-form and B-form helices, respectively (18). Few MD studies have been performed on ssRNA, the majority of which use the AMBER force field (19,20) to explore the impact of chemical modifications such as peptide nucleic acids (PNA) and O2 0 -methylation (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, base stacking has been proposed to influence the reactivity of phosphodiester bonds of oligonucleotides [5]. H-Bonding, as suggested in the present article, is not an alternative for base stacking, but stacking and other intramolecular forces most likely determine the overall shape of the molecule.…”
mentioning
confidence: 87%
“…Single-stranded sequences may also form sufficiently stable helices in cases where the successive bases are stacked upon each other [4]. Theoretically calculated stacking strengths have been shown to correlate roughly with the reactivity of phosphodiester bonds [5]. The poor reactivity of certain sequences can, hence, be rationalized by the rigidity of the structure, but the observation that phosphodiester bonds in certain sequences were more reactive than freely rotatable phosphodiester bonds of oligo-U is more difficult to understand.…”
mentioning
confidence: 99%